Interdisciplinary interactions, social systems and technical infrastructure required for successful implementation of mobile stroke units: A qualitative process evaluation. Issue 3 (17th January 2023) - Bagot, Kathleen L.; Purvis, Tara; Hancock, Shaun; Zhao, Henry; Coote, Skye; Easton, Damien; Campbell, Bruce C. V.; Davis, Steve M.; Donnan, Geoff A.; Foster, Shane; Langenberg, Francesca; Smith, Karen; et al.
Abstract: Rationale: Mobile stroke units (MSUs) are increasingly being implemented to provide acute stroke care in the prehospital environment, but a comprehensive implementation evaluation has not been undertaken. Aim: To identify successes and challenges in the pre‐ and initial operations of the first Australian MSU service from an interdisciplinary perspective. Methods: Process evaluation of the Melbourne MSU with a mixed‐methods design. Purposive sampling targeted key stakeholder groups. Online surveys (administered June–September 2019) and semistructured interviews (October–November 2019) explored experiences. Directed content analysis (raters' agreement 85%) and thematic analysis results are presented using the Interactive Sociotechnical Analysis framework. Results: Participants representing executive/program operations, MSU clinicians and hospital‐based clinicians completed 135 surveys and 38 interviews. Results converged, with major themes addressing successes and challenges: stakeholders, vehicle, knowledge, training/education, communication, work processes and working relationships. Conclusions: Successes and challenges of establishing a new MSU service extend beyond technical, to include operational and social aspects across prehospital and hospital environments.